Do gaze behaviours during action observation predict interpersonal motor resonance?. Issue 1 (12th August 2020) - Bekkali, Soukayna; Youssef, George J; Donaldson, Peter H; He, Jason; Do, Michael; Hyde, Christian; Barhoun, Pamela; Enticott, Peter G
Abstract: Interpersonal motor resonance (IMR) is a common putative index of the mirror neuron system (MNS), a network containing specialised cells that fire during both action execution and observation. Visual content inputs to the MNS, however, it is unclear whether visual behaviours mediate the putative MNS response. We aimed to examine gaze effects on IMR during action observation. Neurotypical adults ( N =  99; 60 female) underwent transcranial magnetic stimulation, electromyography, and eye-tracking during the observation of videos of actors performing grasping actions. IMR was measured as a percentage change in motor evoked potentials (MEPs) of the first dorsal interosseous muscle during action observation relative to baseline. MEP facilitation was observed during action observation, indicating IMR (65.43%, SE = 11.26%, P  < 0.001). Fixations occurring in biologically relevant areas (face/hand/arm) yielded significantly stronger IMR (81.03%, SE = 14.15%) than non-biological areas (63.92%, SE = 14.60, P  = 0.012). This effect, however, was only evident in the first of four experimental blocks. Our results suggest that gaze fixation can modulate IMR, but this may be affected by the salience and novelty of the observed action. These findings have important methodological implications for future studies in both clinical and healthy populations.